Role of CD40(L)-TRAF signaling in inflammation and resolution—a double-edged sword - Strohm, Lea; Ubbens, Henning; Münzel, Thomas; Daiber, Andreas; Daub, Steffen (Frontiers in Pharmacology, 2022)
Cardiovascular diseases (CVD) and cardiovascular risk factors are the leading cause of death in the world today. According to the Global Burden of Disease Study, hypertension together with ischemic heart and cerebrovascular diseases is responsible for approximately 40% of all deaths worldwide. The major pathomechanism underlying almost all CVD is atherosclerosis, an inflammatory disorder of the vascular system. Recent large-scale clinical trials demonstrated that inflammation itself is an independent cardiovascular risk factor. Specific anti-inflammatory therapy could decrease cardiovascular mortality in patients with atherosclerosis (increased markers of inflammation). Inflammation, however, can also be beneficial by conferring so-called resolution, a process that contributes to clearing damaged tissue from cell debris upon cell death and thereby represents an essential step for recovery from, e.g., ischemia/reperfusion damage. Based on these considerations, the present review highlights features of the detrimental inflammatory reactions as well as of the beneficial process of immune cell-triggered resolution. In this context, we discuss the polarization of macrophages to either M1 or M2 phenotype and critically assess the role of the CD40L-CD40-TRAF signaling cascade in atherosclerosis and its potential link to resolution. As CD40L can bind to different cellular receptors, it can initiate a broad range of inflammatory processes that may be detrimental or beneficial. Likewise, the signaling of CD40L downstream of CD40 is mainly determined by activation of TRAF1-6 pathways that again can be detrimental or beneficial. Accordingly, CD40(L)-based therapies may be Janus-faced and require sophisticated fine-tuning in order to promote cardioprotection.